Pleuroskopi Sebagai Tindakan Diagnostik pada Paru - Hafis Herdiman; Oea Khairsyaf; Russilawati Russilawati (Poltekkes Kemenkes Padang, 2021)
Pleuroscopy, also known as medical thoracoscopy, is a minimally invasive procedure that is used to examine and biopsy the pleural cavity as well as to perform therapeutic interventions. This procedure has a near-perfect diagnostic accuracy in malignant pleural effusions and tuberculosis. With a mortality rate of 0.1%, the complication rate is low (2% - 5%) and usually mild (subcutaneous emphysema, bleeding, infection). Objective : Increase knowledge of pleuroscopy as a diagnostic and therapeutic tool in lung disease. Method : This paper is based on a review of the literature on pleuroscopy. Conclusion : Pleuroscopy is a minimally invasive procedure that can be used to examine and biopsy the pleural cavity, as well as for therapeutic intervention. Complications are uncommon and usually minor. Sugestion : Other articles are required to increase knowledge about pleuroscopy in order to obtain more knowledge.